Capacity development on feeds and forages, manure management and animal health techniques for farmers in Mai Son District, Son La Province - Nguyen, Thi Hien; Nguyen, Thi Bich Hoai; Luu, Thi Huong; Lo, Thi Hoa; Lo, Quang Thanh; Dao, Thi Thu Hang; Duncan, Alan J.; Peters, Michael; Atieno, Mary (International Livestock Research Institute, 2024)
The CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING) initiative being implemented in Son La Province, Vietnam, aims to transform the livestock value chain in the Northwest Highlands of Vietnam towards greater livestock productivity, adaptation, equity, and sustainability. This aligns with the development goals of the agricultural sector in both Mai Son District and Son La Province. The work in the locality focuses on developing livestock value chains and commercially oriented cattle production initiatives (Resolution No. 75/2023/NQ-HDND dated 8 December 2023, Provincial People's Council) and encourages the implementation of sustainable agricultural practices, including scaling forages for livestock feed and reducing soil erosion (Official Letter No. 1587/UBND-NN dated 11 May 2024, People's Committee of Mai Son District).